My prison, my home : one woman's story of captivity in Iran - Isfandiyari, Halah (New York : Ecco, 2009)
On December 31, 2006, Isfandiyari's life changed. It was believed she was part of an American conspiracy for'regime change' in Iran. After weeks of interrogation, she was detained at the notorious Evin Prison, where she spent 105 days in solitary confinement.
Keywords: Isfandiyari, Halah; Women political prisoners -- Iran -- Biograph; Political prisoners -- Iran -- Biography; Iranian American women -- Biography; Iranian American authors -- Biography; Islam and politics -- Iran; Iran -- Politics and government -- 21st century